A Pilot Study Using a Web Survey to Identify Characteristics That Influence Hypogonadal Men to Initiate Testosterone Replacement Therapy - Raymond C. Rosen PhD; Allen D. Seftel MD; Dustin D. Ruff PhD; David Muram MD (American Journal of Men's Health, 2018)
Men with hypogonadism (HG) who choose testosterone replacement therapy (TRT) may have distinct characteristics that provide insight as to why they may/may not initiate therapy. The aim of the current study was to identify trends in patient characteristics and attitudes in men diagnosed with HG who initiated TRT (TRT+) compared with men who were diagnosed with HG but did not initiate TRT (TRT−). The market research-based online survey conducted between 2012 and 2013 included patients from a Federated Sample, a commercially available panel of patients with diverse medical conditions. The current analysis was composed of two groups: TRT+ ( n = 155) and TRT− ( n = 157). Patient demographics, clinical characteristics, and attitudes toward HG and TRT were examined as potential predictors of primary adherence in men with HG; cohorts were compared by using Fisher’s exact test. Significant associations among sexual orientation, relationship status, educational level, presence of comorbid erectile dysfunction, area of residence, and TRT initiation were present ( p ≤ .05). College-educated, heterosexual, married men with comorbid erectile dysfunction living in suburban and urban areas were more likely to initiate treatment. The most bothersome symptoms reported were lack of energy (90% vs. 81%, p = .075), decreased strength and endurance (86% vs. 76%, p = .077), and deterioration in work performance (52% vs. 31%, p = .004); lack of energy prompted men to seek help. Patients (48%) in the TRT+ group were more knowledgeable regarding HG as compared with TRT− respondents (14%, p < .001), and most men obtained their information from a health care professional (89% vs. 82%, p = .074). The current analysis identified distinct demographic and clinical characteristics and attitudes among TRT users compared with men who were diagnosed with HG yet remained untreated.